2010
DOI: 10.1051/0004-6361/200912435
|View full text |Cite
|
Sign up to set email alerts
|

Dust tori in radio galaxies

Abstract: Aims. We investigate the quasar -radio galaxy unification scenario and detect dust tori within radio galaxies of various types. Methods. Using VISIR on the VLT, we acquired sub-arcsecond (∼0.40 ) resolution N-band images, at a wavelength of 11.85 μm, of the nuclei of a sample of 27 radio galaxies of four types in the redshift range z = 0.006−0.156. The sample consists of 8 edge-darkened, low-power Fanaroff-Riley class I (FR-I) radio galaxies, 6 edge-brightened, class II (FR-II) radio galaxies displaying low-ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 110 publications
(120 reference statements)
5
40
0
Order By: Relevance
“…Therefore, in the light of the current results, we will discuss probable mechanisms responsible for the observed and possibly intrinsic differences. There is strong evidence that the dusty obscuring torus in low luminosity AGN is absent or is thinner than expected in higher luminosities (e.g., Whysong & Antonucci 2004;Elitzur & Shlosman 2006;Perlman et al 2007;van der Wolk et al 2010). Accordingly, all low luminosity AGN should have been Type I sources, which of course is not the case.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, in the light of the current results, we will discuss probable mechanisms responsible for the observed and possibly intrinsic differences. There is strong evidence that the dusty obscuring torus in low luminosity AGN is absent or is thinner than expected in higher luminosities (e.g., Whysong & Antonucci 2004;Elitzur & Shlosman 2006;Perlman et al 2007;van der Wolk et al 2010). Accordingly, all low luminosity AGN should have been Type I sources, which of course is not the case.…”
Section: Discussionmentioning
confidence: 98%
“…There is a dust torus around this BLRG extending to ∼ 0.5 kpc (van der Wolk et al 2010) and an emission line region extending to ∼ 100 kpc (Prieto & Zhao 1997). It is an FRII lying in a weak environment (Bgq ∼ 80 -Ramos Almeida et al 2013).…”
Section: Appendix A: Notes On Individual Sourcesmentioning
confidence: 91%
“…Alternatively, we would have to isolate the torus spatially from more extended emission. This has been attempted for nearby type 2 AGN (van der Wolk et al 2010) where such an extended component has indeed been identified at λ rest = 12 μm. Both types of observation are beyond the reach of current facilities for our samples.…”
Section: Stellar and Extended Warm Dust Emissionmentioning
confidence: 99%